Potensi UMKM Kontribusi BMT Sidogiri Cabang Depok dalam Meningkatkan Produktivitas Bisnis Lokal - Pratama, Dito Alif (Prodi Ekonomi Syariah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2023)
This research investigates the role of Baitul Maal Wattamwil (BMT) UGT Sidogiri Branch in Sawangan Depok in enhancing the productivity of Micro, Small, and Medium Enterprises (MSMEs) and its impact on local economic development. The study employs a descriptive analysis method based on quantitative data collected from BMT's financial reports and MSME members who received financing in the form of Barakah Business Capital (MUB). Additionally, insights into BMT's role in empowering MSMEs were obtained through interviews with BMT management and MSME members. The findings reveal that BMT UGT Sidogiri Branch significantly contributes to enhancing MSME productivity. Providing MUB financing offers substantial benefits to MSMEs, helping them improve their businesses and support local economic development. BMT successfully facilitates collaboration among members, strengthens economic synergies, and places special emphasis on the welfare of MSME members through a profit-sharing system based on Sharia principles. Despite its positive contributions, the research identifies several challenges faced by BMT Sidogiri, including members who are urban dwellers or newcomers, competition with daily banks/usurers, and technological limitations. Nevertheless, BMT UGT Sidogiri has implemented strategic measures, such as a family-oriented approach and technology integration, to address these challenges.